PENINGKATAN MOTIVASI BELAJAR MELALUI PEMBELAJARAN MATEMATIKA REALISTIK PADA SISWA KELAS IX SMP NEGERI 1 SUMBERGEMPOL KABUPATEN TULUNGAGUNG - Suwoto Suwoto (LP2M IAIN Tulungagung, 2015)
This study aimed to describe realistic mathematics learning approach on the topic of statistics and opportunities that can improve motivation and learning achievement and describe the tips of teachers in motivating students. The results of this study, among others, the learning of mathematics using realistic mathematics approach can increase student motivation, problem solving through exploration activities in daily life by setting discussion through study groups and task based on the capabilities of the students. Teachers try to create a pleasant classroom atmosphere and provide an appreciation of the students' efforts. The students had a positive response to the realistic mathematics learning process.Kata kunci: Matematika realistik, motivasi, pembelajaran